The Influence of ISLE-based STEM Physics Learning on Students' Understanding of Physics Concepts - Sari, Novianti Puspita; Gaa, Fatimah; Sene, Marieta Tiara; Liu, An Nisaa Al Mu'min (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2024)
This research aims to provide an overview and determine the influence of ISLE (Investigative Science Learning Environment) based STEM (Science Technology Engineering and Mathematics) physics learning on students' understanding of physics concepts. This research is a quantitative descriptive study using the one group pretest-posttest method. The population in this study were students of class XI Science at MAN Ende for the 2024/2025 academic year and the sample was students of class. Sampling in this research used purposive sampling technique. The data collection method consists of administering tests and LKPD. The data obtained from the research sample was in the form of test scores on students' understanding of physics concepts on global warming materials. Normality test and t-test are the data analysis techniques used. From the results of data analysis, it is known that ISLE based STEM physics learning has an effect on students' ability to understand physics concepts according to the One-Sample Test carried out with sig. (One-Sided p) is 0.001 < 0.05. Students' ability to understand physics concepts increased after implementing ISLE-based STEM physics learning with an average pretest score of 57.119 and an average posttest of 89.381 with the difference between the posttest and pretest scores being 32.252 points. While working on the LKPD students are more active in working with their team in solving problems and students are trained to understand the procedures for working on them. Apart from that, by implementing this learning, it can encourage students to hone their own thinking patterns so that they are able to explain the students' own understanding of physics concepts based on what they have observed and understood.